The relationship between left ventricular outflow tract gradient and sudden cardiac death in childhood hypertrophic cardiomyopathy. (25th November 2020) - Norrish, G; Ding, T; Field, E; O'Mahony, C; Elliott, P.M; Omar, R; Kaski, J.P
Abstract: Background: The most common mode of death in childhood hypertrophic cardiomyopathy (HCM) is sudden cardiac death (SCD). Left ventricular outflow tract obstruction (LVOTO) is an established risk factor for SCD in adults with the disease. In contrast, the prognostic implications of LVOTO in childhood disease is unclear, with recent studies suggesting that it may have an inverse relationship with the risk of SCD. Purpose: The aim of this study was to explore the role of LVOTO and the risk of SCD in childhood HCM. Methods: A multi-centre, retrospective, longitudinal cohort of 871 children (diagnosed with HCM <16 years of age) was used to explore the relationship between SCD and LVOTO (LVOT gradient ≥30mmHg). Results: 189 patients (23%) had LVOTO, which was mild (30–50mmHg), moderate (50–100mmHg) or severe (>100mmHg) in 58 (6.7%), 98 (11.3%) and 33 (3.8%), respectively. The risk of SCD showed an inverse relation to LVOT gradient severity compared to those with no obstruction: mild HR 1.75 (95% CI 0.89–3.44), moderate HR 1.04 (95% 0.55–1.98), and severe HR 0.7 (0.36–1.35) [figure].On univariable analysis [table] LVOTO was associated with heart failure symptoms (NYHA>1) [p <0.001], maximal wall thickness (MWT) [p <0.001], left atrial (LA) diameter [p <0.001], and future myectomy occurring during follow up [p <0.001]. The inverse relationship observed was not altered by the presence or absence of other traditional risk factors. Conclusions: LVOTO appears to have a complex relationship with the risk of SCD in childhood HCM, with multiple contributing factors. The pathophysiological mechanisms behind this observation need further exploration, which may be limited by low patient numbers Funding Acknowledgement: Type of funding source: Other. Main funding source(s): British Heart Foundation